Energy consumption and heat island effect mitigation analysis of different roofs considering superposition coupling - Zhao, Shanguo; Zhang, Xiaosong (Frontiers in Energy Research, 2023)
Building energy, especially air conditioning energy accounts for a remarkable proportion in the total social energy consumption. As a typical urban environmental problem, heat island effect is also posing a threat to human sustainable development. Accounting for more than 20% of the whole urban area, roof plays an important role in alleviating urban heat island effect and reducing building energy consumption. A simulation model is established based on typical residential community to analyze the triple positive effects of cool roof and green roof on building energy conservation in different climate zones in China. Results show that triple effect on building energy conservation by mitigating the heat island effect for cool roof and green roof is remarkable：reducing direct heat gain from roof, reducing heat transfer from enclosure and improving the coefficient of performance . In cold areas, hot summer and cold winter areas and hot summer and warm winter areas, cool roof can reduce the regional ambient temperature by 2 ℃, 2.3 ℃ and 2.6 ℃ and that for green roof is 1 ℃, 1.1 ℃ and 1.2 ℃. For building energy conservation the triple saving effect for cool roof and green roof can achieve 11.0%, 11.7%, 12.6% and 9.4%, 9.2% and 9.3% respectively. Cool roof performs better in low latitude areas because of the increasing solar radiation, while for green roof it remains a stable performance.